'Care is not a burden': a 7-4-7 framework of action for operationalising the Triple R. Issue 1 (4th May 2022) - Chopra, Deepta; Krishnan, Meenakshi
ABSTRACT: Our research on government policy responses to address the increase in women's unpaid care and domestic work during COVID-19, across 59 countries of Asia and the Pacific, shows that less than 30 per cent of measures are care-sensitive and of these only 12 per cent are gender-differentiated. From this analysis, this paper proposes a care-integral approach to ensure gender-transformative outcomes. This approach comprises a unique three-tier framework for policy action constituting: (1) seven foundational care normative principles, (2) typology of four care-sensitive policy categories, and (3) seven levers of change to guide implementation. Together this 7-4-7 framework presents comprehensive strategies for policymakers to operationalise the Triple R agenda of 'Recognise', 'Reduce', and 'Redistribute' unpaid work. Further, this paper makes a unique contribution by redirecting attention of the Triple R approach on quantity of care, to make a case for improving the overall quality of care.